PENGARUH MOTIVASI, KEDISIPLINAN DAN GAYA KEPEMIMPINAN TERHADAP PRESTASI KERJA PEGAWAI PADA DINAS SOSIAL TENAGA KERJA DAN TRANSMIGRASI KABUPATEN BATANG HARI - Suharyono Suharyono; Hapzi Ali (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
This research purposes to desription motivation, discipline and leadership on work achievement in the Department Of The District Social Man Powet and Transmigration Batang Hari Regency. The sampling chooses 69 officer to be teken the number of population 218 officers, sampling technic to use Proportional random sampling. The research instrument chooses questioner, to be built in scala 69-345, scala score 69 for very no bad reaction, and score 345 for very good reaction. The technic of the date analysis chooses descriptive analysis and doble regrasi analysis. The result of this research show both motivation and discipline of the officers in the Department of the Distric Social Man Powet and Transmigration Batang Hari Regency can be categoried good. The Main motivation of the officer to be supported by the high of the opportunity to built self potency to work, whereas discipline to be shown by the acceptance of the officer will be punished if the break the rule anthe arrangement to be used even the leadership the behavior has done dominance in the usual organization is delegatif behavior. That is by giving the job competience and the big responsibility to be given by the officer to do the work. The result of hipotesis show that motivation, discipline and leadership to be proved positive in influence and significant to carrier of the officer and among variable of motivation, discipline and leadership to appear motivation is a dominant variable to influence the carrier of the officer in  the Department Of The Distric Social Man Powet and Transmigration Batang Hari Regency.Keywords : Motivation,  Dicipline and  Leadership on work achievement.